Eagle strategy-based crow search algorithm for UCP: integration of pumped storage units in smart grid environment - Rizki, Adil; Habachi, Rachid; Tahiry, Karim; Echchatbi, Abdelwahed (Bulletin of Electrical Engineering and Informatics, 2025)
This paper proposes a hybrid eagle strategy with crow search algorithm (ES-CSA) as local optimizer to solve the unit commitment problem (UCP) in power systems. The algorithm aims to minimize total operational costs while considering pumped storage units as spinning reserves. The proposed methodology combines the exploration capability of ES with CSA's local search efficiency to determine optimal generator scheduling and power dispatch. The approach is validated using standard test cases from the literature, demonstrating improved convergence and cost reduction compared to existing methods. Results confirm the effectiveness of integrating pumped storage units in reducing overall system costs while maintaining reliable operation.